2010
DOI: 10.1007/s00425-010-1242-6
|View full text |Cite
|
Sign up to set email alerts
|

PIRL1 and PIRL9, encoding members of a novel plant-specific family of leucine-rich repeat proteins, are essential for differentiation of microspores into pollen

Abstract: Plant intracellular Ras-group-related leucine-rich repeat proteins (PIRLs) are a plant-specific class of leucine-rich repeat (LRR) proteins related to animal and fungal LRRs that take part in developmental signaling and gene regulation. As part of a systematic functional study of the Arabidopsis thaliana PIRL gene family, T-DNA knockout mutants defective in the closely related PIRL1 and PIRL9 genes were identified and characterized. Pirl1 and pirl9 single mutants displayed normal transmission and did not exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 77 publications
7
29
1
Order By: Relevance
“…However, after that initial period of normal development, pirl1;pirl9 microspores produced by this genotype consistently arrest and are unable to complete the first pollen mitosis. Consistent with the late-microspore onset of the mutant phenotype, analysis of pirl1;pirl9 phenotype segregation in qrt1 tetrads confirmed that abnormalities originate after meiosis, thus indicating that these PIRL genes have essential function in the developing haploid microspores (Forsthoefel et al 2010).…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…However, after that initial period of normal development, pirl1;pirl9 microspores produced by this genotype consistently arrest and are unable to complete the first pollen mitosis. Consistent with the late-microspore onset of the mutant phenotype, analysis of pirl1;pirl9 phenotype segregation in qrt1 tetrads confirmed that abnormalities originate after meiosis, thus indicating that these PIRL genes have essential function in the developing haploid microspores (Forsthoefel et al 2010).…”
Section: Introductionsupporting
confidence: 56%
“…Pirl T-DNA knockout alleles used in this study have been described previously and shown to be knockout alleles based on reverse transcription-PCR analysis of disrupted loci (Forsthoefel et al 2010). Pirl1-1 and pirl9-1 are in the Wassilewskija (Ws) ecotype, and pirl1-2 and pirl9-2 are in Columbia.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations